2014
DOI: 10.1177/0218492314527991
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative tranexamic acid in pediatric bloodless cardiac surgery

Abstract: Intraoperative tranexamic acid administration was effective for blood conservation, and improved postoperative clinical outcomes in pediatric bloodless cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 27 publications
(32 reference statements)
1
14
0
Order By: Relevance
“…20 In a retrospective study Hasegawa and colleagues evaluated the effectiveness of intraoperative TXA in blood-less cardiac surgery in children and found that intraoperative TXA was effective for both blood conservation and post-op clinical outcomes. 21 In another study, Patel and colleagues studied to determine the effectiveness of Topical TXA in paediatric cardiac surgery. They concluded that the combination of low dose systemic TXA and topical TXA intrapericadially before chest closure was the best.…”
Section: Discussionmentioning
confidence: 99%
“…20 In a retrospective study Hasegawa and colleagues evaluated the effectiveness of intraoperative TXA in blood-less cardiac surgery in children and found that intraoperative TXA was effective for both blood conservation and post-op clinical outcomes. 21 In another study, Patel and colleagues studied to determine the effectiveness of Topical TXA in paediatric cardiac surgery. They concluded that the combination of low dose systemic TXA and topical TXA intrapericadially before chest closure was the best.…”
Section: Discussionmentioning
confidence: 99%
“…Bloodless paediatric cardiac surgery has been performed successfully with the use of miniature circuits. 13,14,18,22 At our institution, miniature CPB circuits were not utilised at the time of the audit. Perhaps this was the reason for only 1.9% of cardiac surgical cases having bloodless surgery in our study.…”
Section: Discussionmentioning
confidence: 99%
“…11 The implementation of blood-conservation strategies to reduce rates of transfusion of blood products in paediatric cardiac surgery is recognised by the WHO. 12 These strategies have made it possible to perform bloodless paediatric cardiac surgery on CPB, 13 and have also been used successfully in Jehovah's Witness patients. 14,15 Blood-transfusion guidelines are available for adult cardiac surgery patients, 16 but could not be found for paediatric patients.…”
mentioning
confidence: 99%
See 2 more Smart Citations